Atypical scrapie in Australia. Issue 12 (3rd November 2016) - Cook, RW; Bingham, J; Besier, AS; Bayley, CL; Hawes, M; Shearer, PL; Yamada, M; Bergfeld, J; Williams, DT; Middleton, DJ
Abstract : Background: Since its initial detection in Norway in 1998, atypical scrapie ('atypical/Nor98 scrapie') has been reported in sheep in the majority of European countries (including in regions free of classical scrapie) and in the Falkland Islands, the USA, Canada, New Zealand and Australia. Case series: The diagnosis in Australia of atypical scrapie in four Merino and one Merino‐cross sheep showing clinical signs of neurological disease was based on the detection of grey matter neuropil vacuolation (spongiform change) in the brain (particularly in the molecular layer of the cerebellar cortex) and associated abnormal prion protein (PrP Sc ) deposition in both grey and white matter. Changes were minimal in the caudal brainstem, the predilection site for lesions of classical scrapie. Conclusion: The distinctive lesion profile of atypical scrapie in these five sheep highlights the diagnostic importance of routine histological evaluation of the cerebellum for evidence of neuropil vacuolation and associated PrP Sc deposition in adult sheep with suspected neurological disease.